The impacts of GM foods: Results from a randomized controlled trial of Bt eggplant in Bangladesh - Ahmed, Akhter; Hoddinott, John F.; Abedin, Naveen; Hossain, Nusrat (Agricultural and Applied Economics Association, 2021)
We implemented a cluster randomized controlled trial to assess the impact of genetically modified eggplant (Bt brinjal) in Bangladesh. Our two primary outcomes were changes in yield and in pesticide costs. Cultivation of Bt brinjal raises yields by 3,564 kg/ha. This statistically significant impact is equivalent to a 51% increase relative to the control group. There is a statistically significant fall in pesticide costs, 7,175 Taka per hectare (85 USD per ha), a 37.5% reduction. Yield increases arise because Bt farmers harvest more eggplant and because fewer fruits are discarded because they are damaged. Bt brinjal farmers sell more eggplant and receive a higher price for the output they sell while incurring lower input costs, resulting in a 128% increase in net revenues. Bt brinjal farmers used smaller quantities of pesticides and sprayed less frequently. Bt brinjal reduced the toxicity of pesticides as much as 76%. Farmers growing Bt brinjal and who had pre‐existing chronic conditions consistent with pesticide poisoning were 11.5% points less likely to report a symptom of pesticide poisoning and were less likely to incur cash medical expenses to treat these symptoms. Our results are robust to changes in model specification and adjustment for multiple hypothesis testing. We did not find evidence of heterogeneous effects by farmer age, schooling, or land cultivated. Bt brinjal is a publicly developed genetically modified organism that conveys significant productivity and income benefits while reducing the use of pesticides damaging to human and ecological health.